AN ANALYSIS OF TAX COMPLIANCE AMONG MSMES IN BEKASI CITY BASED ON THE THEORY OF PLANNED BEHAVIOR - Nancy Neorita Siagian; Lin Oktris (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the effect of tax morality, tax literacy, and income level on taxpayer compliance, with religiosity as a moderating variable. This study focuses on Micro, Small, and Medium Enterprises (MSMEs) taxpayers who play an important role in national tax revenue. Data were collected through questionnaires distributed to a number of MSME taxpayers and analyzed using moderation regression methods. The population in this study was MSMEs that were taxpayers in the Bekasi city area. The sample in this study consisted of 390 taxpayers. Data analysis in this study used the SMARTPLS Version 3.2.9 analysis tool. The results of the study indicate that tax morale and tax literacy have a positive and significant effect on taxpayer compliance, while income level has no effect on taxpayer compliance. Meanwhile, the results of the interaction of moderating variables show that religiosity strengthens the effect of tax morale on taxpayer compliance and weakens the effect of tax literacy and income level on taxpayer compliance.